Pengaruh Manajemen Keuangan dan Pembelajaran Kewirausahaan Terhadap Intensi Wirausaha Mahasiswa Universitas Jambi - Kuswanto Kuswanto; Suratno; Ayu Asmarani (Jurnal Bisnis dan Kewirausahaan, 2022)
This study aims to describe the effect of financial management and entrepreneurial learning on the entrepreneurial intentions of students of the Entrepreneurship Student Program (PMW) Jambi University. This research is a quantitative research using the Ex-post facto method. The study was conducted on students participating in the PMW of Jambi University in 2021, as many as 86 business groups. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that either partially or simultaneously the variables of financial management and entrepreneurial learning have a significant effect on the entrepreneurial intentions of students of the Jambi University Student Entrepreneurship Program (PMW). Based on the results of this study, it is recommended that universities pay great attention to entrepreneurship learning as a transformation of knowledge and coaching in fostering student interest in entrepreneurship. As prospective entrepreneurs, students are required to be able to manage finances as one of the keys to success in entrepreneurship.